2014
DOI: 10.1016/j.ijnurstu.2013.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The nursing work of hospital-based clinical practice guideline implementation: An explanatory systematic review using Normalisation Process Theory

Abstract: This review demonstrates the feasibility and benefits of theory-led review of studies of nursing practice, and proposes a dynamic model of implementation. Normalisation Process Theory supports the analysis of nursing work. It characterises mechanisms by which work is made coherent and meaningful, is formed around sets of relational commitments, is enacted and contextualised, and is appraised and reconfigured. It facilitates such analysis from within the frame of nursing knowledge and practice itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 38 publications
5
72
0
1
Order By: Relevance
“…We argue that research use through EB guidelines integrated through a tool such as the huddle board might contribute to improved sustainability of guidelines through persistent routinization of action. This is consistent with other studies suggesting that routinization or normalization increases clinicians' use of guidelines and stimulate guideline sustainability (Fleiszer, Semenic, Ritchie, Richer, & Denis, 2015;May, Sibley, & Hunt, 2014).…”
Section: Standardization and Routinization May Promote Ebp At The Ssupporting
confidence: 91%
“…We argue that research use through EB guidelines integrated through a tool such as the huddle board might contribute to improved sustainability of guidelines through persistent routinization of action. This is consistent with other studies suggesting that routinization or normalization increases clinicians' use of guidelines and stimulate guideline sustainability (Fleiszer, Semenic, Ritchie, Richer, & Denis, 2015;May, Sibley, & Hunt, 2014).…”
Section: Standardization and Routinization May Promote Ebp At The Ssupporting
confidence: 91%
“…A systematic review of nursing interventions designed to normalize implementation of clinical guidelines highlighted the need to: integrate the change into the current workflow; involve and engage the relevant communities of practice and recognize the reason for that engagement; and build shared commitments across professional boundaries [31]. Another study interviewed nurses to examine factors that facilitate the effective implementation of clinical guidelines [32].…”
Section: Discussionmentioning
confidence: 99%
“…It develops by adding many tasks not necessarily related to one another, which makes it diffi cult to remember them and leads to a lack of clarity as to who is allowed (or not allowed) to perform what task (which might explain the fi nding that sometimes nurses perform tasks that they are not authorized to do). May, Sibley & Hunt emphasized that assimilating authority in the fi eld must be associated with tasks that are already being performed and are integrated into the workfl ow [2]. When the tasks are performed sporadically and are not necessarily part of the overall work process, it is almost impossible to systematically remember everything that is permitted.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that academic education was a predictor for a nurse's attitudes. found that the physicians had greater diffi culty transferring diagnostic tasks to nurses, while some 45% of the physicians agreed that tasks such as writing prescriptions and outlining treatment could be done by specialist nurses [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation